Headache associated with airplane travel - Berilgen, MS; Müngen, B (Blackwell Publishing, 2006)
This study presents six cases of headache that appeared only during flights and was not associated with other headache forms. The cases had severe headache attacks during some flights, when the plane was landing and taking off, with a unilateral and generally orbital and/or supraorbital localization. The attacks lasted between 15 and 20 min on average and recovered spontaneously, without any accompanying sign. We think that barotrauma caused by pressure changes in the cabin during take-off and landing could affect ethmoidal nerves (branching from the ophthalmic branch of the trigeminal nerve) that carry the senses of the mucosa on the inner surface of the paranasal sinuses, and/or nociceptors in ethmoidal arteries, thereby activating the trigeminovascular system and leading to headache.
Keywords: airplane; atmospheric conditions; barotrauma; headache